Electrical characterization of dielectrically isolated silicon substrates containing buried metallic layers - Goh, Wang Ling (2009)
Dielectrically isolated substrates containing buried highly conducting WSi2 layers are characterized for the first time using MOS capacitors. The active silicon layer is approximately 3 µm thick with a buried WSi2 layer 120 mm thick adjacent to the isolation layer. The buried metal forms the back contact of the capacitor and excellent MOS characteristics are observed. Minority carrier lifetimes in excess of 200 µs were measured indicating the suitability of these substrates for use in device manufacture.